Fulfillment of Living for Minor Marriages Perspective of The Law. No.1 of 1974 and a Compilation of Islamic Law - Azzaul, Azwin Ridwan; Busriyanti, Busriyanti; Faisol, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Livelihood is a consequence of obligations that arise, one of which is with the marriage bond. But when the marriage is carried out by a minor, of course, other more complex problems arise. Underage marriage, which is mainly carried out by boys, makes it burdened with the obligation to provide when it should be still a student or college student. It also widens job opportunities in the field which is difficult due to the age of the minor. This condition is even worse if the parents of the couple are families who are still on the poverty line. So, the government must take the government seriously to respond to this problem considering that marriages carried out can occur legally because marriage dispensation is allowed. The purpose of this study is to analyze the causes of underage marriage and the concept of fulfillment when viewed from Marriage Law No. 1 of 1974 with the Compilation of Islamic Law. The research method carried out in this study is qualitative with a normative juridical approach. Data collection techniques through literature studies, by inventorying various main and supporting library materials related to the focus of the problem. Data analysis techniques are processed and discussed using descriptive methods. The results showed several factors causing underage marriage which was dominated by pregnancy out of wedlock, economy, technological and information advances as well as culture and religion. As for the fulfillment of bread, the state only regulates, in general, these provisions, both in Marriage Law No. 1 of 1974 and the Compilation of Islamic Law. Fulfilling the income carried out by the husband does not provide distinction to the husband who is underage but is legalized by the government with the marriage dispensation given. Therefore, it is necessary to revise the regulation so that it can guarantee the rights of every citizen are fulfilled.